2002
DOI: 10.1152/ajpheart.01082.2001
|View full text |Cite
|
Sign up to set email alerts
|

EDHF, but not NO or prostaglandins, is critical to evoke a conducted dilation upon ACh in hamster arterioles

Abstract: Vasomotor reactions upon focal stimulation of arterioles have been shown to be conducted along the vascular wall. Such a conduction, which is assumed to reflect the spread of electrical signals, may contribute to coordination of responses within a vascular segment. We aimed to identify which endothelial autacoid(s) act as mediators of the local and conducted dilator responses, respectively. To this end, arterioles in the hamster cremaster microcirculation were locally stimulated with endothelium-dependent [ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
76
2
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(88 citation statements)
references
References 33 publications
9
76
2
1
Order By: Relevance
“…Inhibition of NO synthase did not reduce local or remote acetylcholine dilations. This suggests that NO does not contribute to the initiation or the conduction process in this preparation as was observed similarly in the hamster cremaster (14), but NO may contribute in other tissues (5). Conversely, NO synthase inhibition also did not enhance the conduction of dilations in wild-type mice.…”
Section: Discussionsupporting
confidence: 60%
“…Inhibition of NO synthase did not reduce local or remote acetylcholine dilations. This suggests that NO does not contribute to the initiation or the conduction process in this preparation as was observed similarly in the hamster cremaster (14), but NO may contribute in other tissues (5). Conversely, NO synthase inhibition also did not enhance the conduction of dilations in wild-type mice.…”
Section: Discussionsupporting
confidence: 60%
“…Despite the presence of antioxidant or PKC inhibition, xanthine-induced reduction in NO production was not restored though attenuated relaxation to ACh was improved. This observation suggests that ACh-induced relaxation may be mediated via other mechanism(s) that is independent of NO for example via endothelium-dependent hyperpolarizing factor, or epoxides (Cohen and Vanhoutte, 1995;Hoepfl et al, 2002). However, this speculation is beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 78%
“…1 However, some studies that question the existence of EDHF suggest that electrical coupling of endothelial and smooth muscle cells through gap junctions mediates the activity. The idea that EDHF/EETs activate potassium channels in endothelial cells, leading to either the release of K ϩ , 2-4 or spread of current from endothelial cells, [5][6][7][8][9] to hyperpolarize smooth muscle, has attracted attention, because histological evidence of the existence of gap junctions between endothelial and smooth muscle cells and between endothelial cells was provided. 10,11 It was also reported that hyperpolarization of endothelial cells by injection of current or administration of ACh was conducted downstream to cause dilation of arterioles through endothelial gap junctions, 12,13 a response that was inhibited by removal of the endothelium, or attenuated in arteries of mice deficient in connexin 40, a protein component of endothelial gap junctions.…”
mentioning
confidence: 99%